Economic impacts of mobile broadband innovation: Evidence from the transition to 4G - Jeffrey Eisenach; Robert Kulick (American Enterprise Institute (AEI), 2020)
This study reports estimates from a model of the economic effects of 4G mobile wireless technology adoption in the United States on employment and economic growth and, based on those results, projects the benefits of 5G adoption under different counterfactual scenarios.
Keywords: A; 330; 5G wireless; Economic growth; employment; technology and innovation